Estimation of stature using lower limb measurements in Sudanese Arabs - Ahmed, Altayeb Abdalla (Journal of forensic and legal medicine, 2013)
The estimation of stature from body parts is one of the most vital parts of personal identification in medico-legal autopsies, especially when mutilated and amputated limbs or body parts are found. The aim of this study was to assess the reliability and accuracy of using lower limb measurements for stature estimations. The stature, tibial length, bimalleolar breadth, foot length and foot breadth of 160 right-handed Sudanese Arab subjects, 80 men and 80 women (25–30 years old), were measured. The reliability of measurement acquisition was tested prior to the primary data collection. The data were analysed using basic univariate analysis and linear and multiple regression analyses. The results showed acceptable standards of measurement errors and reliability. Sex differences were significant for all of the measurements. There was a positive correlation coefficient between lower-limb dimensions and stature (P-value < 0.01). The best predictors were tibial length and foot length. The stature prediction accuracy ranged from ±2.75–5.40 cm, which is comparable to the established skeletal standards for the lower limbs. This study provides new forensic standards for stature estimation using the lower limb measurements of Sudanese Arabs.